The main directions of social reporting in enterprises (Zien Journal of Social Sciences and Humanities, 2022)
The study explores the nature of social responsibility. Foreign experience in the formation of non-financial reports is studied. The advantages of external and internal social reporting are also detailed. The importance of social reporting has been explored. The stages of financial reporting were studied and relevant proposals and recommendations were developed.